Cubature Points Based Triangular Spectral Elements: An Accuracy Study (Journal of Mathematical Study, 2019)
We investigate the cubature points based triangular spectral element methodand provide accuracy results for elliptic problems in non polygonal domains usingvarious isoparametric mappings. The capabilities of the method are here again clearlyconfirmed.
Keywords: Spectral element method; simplicial meshes; cubature points; Fekete points; isoparametric mappings.